The Application of Therapeutic Communication to Family Anxiety in Patients in the Intensive Care Unit - Christian Romario; Marthen Preskapu Wela; Maria Dua Riong; Carolus Baga Keupung (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Care in the Intensive Care Unit (ICU) involves complex clinical situations that place patients in critical conditions and simultaneously expose their families to significant psychological stress. Uncertainty regarding prognosis, limited visiting hours, and unfamiliar medical equipment often trigger anxiety among patients’ families, which can affect decision-making, coping ability, and trust in healthcare providers. Nurses play a pivotal role in addressing this anxiety through therapeutic communication, a non-pharmacological intervention that emphasizes empathy, clarity, honesty, and supportive relationships. This study aimed to explore the implementation of nurse therapeutic communication and its meaning in reducing anxiety among families of ICU patients using a descriptive qualitative approach. The study employed a case study design involving purposively selected family members of patients treated in the ICU of Dr. T.C. Hillers Maumere Regional General Hospital. Data were collected through in-depth semi-structured interviews, direct observation of nurse–family interactions, and supporting documentation, including anxiety assessments using the Hamilton Anxiety Rating Scale (HARS). Data were analyzed thematically through data reduction, presentation, and conclusion drawing, with validity ensured through source and method triangulation. The findings revealed that families initially experienced moderate levels of anxiety characterized by fear, confusion, and emotional distress. Following consistent therapeutic communication by nurses, families reported feeling calmer, more informed, and emotionally supported, which was reflected in decreased anxiety levels from moderate to mild. Therapeutic communication was perceived not only as information delivery but also as a form of emotional reassurance and caring presence. In conclusion, therapeutic communication is a crucial component of holistic ICU nursing care that significantly contributes to reducing family anxiety and strengthening nurse family relationships.